Economic analysis of rhizobia and azospirilla co-inoculation in common beans - Matheus Messias; Princewill Chukwuma Asobia; Enderson Petrônio de Brito Ferreira (Bulletin of the National Research Centre, 2023)
Abstract Background Common bean has high production cost, mainly due to the use of inputs like nitrogen fertilizers. An alternative to replace the use of nitrogen fertilizers is the co-inoculation technique. This work aimed to evaluate the economic performance of the co-inoculation of Rhizobium tropici and different doses of Azospirillum brasilense applied at the V2–V3 stage of the common bean. Methods The economic analysis was carried out based on data from five field experiments in five locations in the state of Goiás in Brazil. Treatments consisted of absolute control (AC), N-fertilizer treatment (NfT), single inoculation of R. tropici (Rt), R. tropici + one dose of A. brasilense (Rt + Ab1l), R. tropici + two doses of A. brasilense (Rt + Ab2l), R. tropici + three doses of A. brasilense (Rt + Ab3l) and R. tropici + four doses of A. brasilense (Rt + Ab4l). The economic analysis was carried out based on prices and market indexes, depending on the grain yield of the different treatments. Results The best economic performance was obtained by the co-inoculation Rt + Ab3l, which provided the highest average values of gross revenue (2.471 US$ ha−1), net revenue (2.220 US$ ha−1), and benefit–cost ratio (1.4 US$ US$−1). Conclusions Co-inoculation Rt + Ab3l also showed the lowest production costs (451 US$ ha−1), while the nitrogen treatment with 80 kg ha−1 of N resulted in the highest average production cost (499 US$ ha−1).